2010
DOI: 10.1002/cncr.25212
|View full text |Cite
|
Sign up to set email alerts
|

Increased exposure to bacterial antigen RpL7/L12 in early stage colorectal cancer patients

Abstract: BACKGROUND:Intestinal bacteria have long been implicated in colorectal cancer pathology, and many reports point to a close linkage between Streptococcus bovis biotype I (recently renamed Streptococcus gallolyticus) infections and tumors of the human colon. This work aims to investigate the humoral immune response to this bacterium during different stages of colorectal cancer. METHODS: The presence of serum antibodies against S. bovis antigen RpL7/L12, previously assigned as a potential diagnostic antigen, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 31 publications
0
48
0
1
Order By: Relevance
“…Furthermore, such antigen profiles of Sgg were found to be clearly associated with CRC already present at early polyp status suggesting early involvement of Sgg into the tumour environment (Tjalsma et al, 2006). Major protein antigens of Sgg were identified as HlpA and Rp L7/L12 (Boleij et al, 2010;Tjalsma et al, 2007;Tjalsma et al, 2006), in addition to two unidentified antigens of 22 and 30 kDa size (Garza-González et al, 2012), suggesting further potential for diagnostic tools to detect SBSEC.…”
Section: Invasion/translocation and Immune Response In Cell Culture Amentioning
confidence: 90%
“…Furthermore, such antigen profiles of Sgg were found to be clearly associated with CRC already present at early polyp status suggesting early involvement of Sgg into the tumour environment (Tjalsma et al, 2006). Major protein antigens of Sgg were identified as HlpA and Rp L7/L12 (Boleij et al, 2010;Tjalsma et al, 2007;Tjalsma et al, 2006), in addition to two unidentified antigens of 22 and 30 kDa size (Garza-González et al, 2012), suggesting further potential for diagnostic tools to detect SBSEC.…”
Section: Invasion/translocation and Immune Response In Cell Culture Amentioning
confidence: 90%
“…Proteome and metabolome analyses point toward the increased utilization of glucose and its metabolites together with the amino acid alanine by S. gallolyticus, suggesting that these CRC metabolites are of particular importance for the observed growth advantage. It can be envisaged that this phenomenon may be one of the molecular mechanisms that supports the high incidence of S. gallolyticus infections in CRC patients (16,28). Below, we will speculate how such a mechanism could have its place in the complex ecosystem of the gut.…”
Section: Discussionmentioning
confidence: 95%
“…According to the data of Sobhani et al ( 2011 ) , colorectal cancer patients have an elevated concentration of Bacteroides and Prevotella in their feces. Boleij et al ( 2010 ) revealed the immune response to RpL7/L12 antigen of Streptococcus bovis is more enhanced in subjects with polyps and with I/II colorectal cancer stages in comparison with asymptomatic individuals. Scanlan et al ( 2008 ) found that the microbiota of colorectal cancer subjects and patients with polyposis is less stable in time and has greater diversity compared to the micro fl ora of healthy controls.…”
Section: The Role Of Gut Microbiota In Colorectal Cancer Developmentmentioning
confidence: 97%